High-thermal-conductivity vapor chamber composite material and preparation method thereof
通过使用CuAgYSi合金材料并进行特定的处理,制备出具有高导热和强度的多孔均热板复合材料,解决了传统均热板材料在高效散热方面的不足,实现了更高效的热量传导。
Patent Information
- Application Number
- CN202411571413.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional heat-smoothing plate materials have shortcomings in high strength and high thermal conductivity, and cannot meet the efficient heat dissipation needs of high-power density chips and other equipment.
CuAgYSi alloy material was used, and CuAgYSiMn alloy was formed by Mn plating and heat treatment, followed by dealloyment treatment to obtain a porous high-thermal heat-conducting plate composite material with small-scale communication holes.
The thermal conductivity of the heat-smoothing plate is improved, the specific surface area is increased, and more full contact with the working liquid is achieved, which significantly improves the heat dissipation performance.
Smart Images

Figure CN119433273A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new materials, and in particular to a high thermal conductivity vapor chamber composite material and a preparation method thereof. Background Art
[0002] A heat spreader is a plate-shaped heat transfer device that is formed by injecting a working liquid (i.e., working fluid) into a near-vacuum cavity with a capillary structure inside and is capable of phase change heat transfer. Its main structures include a shell plate, a liquid wick, a liquid-filled tube, and a working fluid. The interior of the heat spreader is a near-vacuum cavity structure with a light weight; it does not require external force to drive it during operation, saving energy; its cavity is welded and sealed, does not leak, and is safe and reliable; its heat transfer method is phase change heat transfer with a high heat transfer coefficient; it can perform two-dimensional heat transfer, has a fast heat conduction speed, and can quickly transfer and distribute the heat from a point heat source on the heat dissipation surface; its external dimensions can be designed according to the specific application scenario; the LED can be directly packaged on it, or it can be tightly fitted to the chip base to reduce contact thermal resistance.
[0003] The heat spreader is mainly used for high-speed transmission hard disk heat dissipation, high-performance microprocessor unit heat dissipation (such as CPU, graphics card, etc.), high-power LED, chip heat dissipation, high-power laser transmitter heat dissipation, satellite energy conversion unit heat dissipation and cooling of medical equipment radiation components. Because it has to withstand the pressure generated during phase change and quickly conduct heat, the heat spreader generally requires good strength and welding performance on the basis of high thermal conductivity. At present, the shell material of the heat spreader is TU2 copper or CuNiP alloy. The former has a high thermal conductivity but insufficient strength, and the latter has acceptable strength but average thermal conductivity. Pure copper powder, pure copper foam, etc. are used as capillary layers inside the heat spreader to achieve efficient heat exchange with the working liquid. As the power density of chips and other devices becomes higher and higher, the heat dissipation demand increases significantly, and traditional heat spreaders cannot meet the performance requirements of high strength and high thermal conductivity. There is an urgent need to develop new high thermal conductivity heat spreader composite materials. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing a high thermal conductivity vapor chamber composite material, which can produce a porous high thermal conductivity vapor chamber composite material having small-scale interconnected pores inside.
[0005] A second object of the present invention is to provide a high thermal conductivity vapor chamber composite material, wherein the porous high thermal conductivity vapor chamber composite material has small-scale interconnected pores inside and has a large specific surface area.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In one aspect, a method for preparing a high thermal conductivity vapor chamber composite material is provided, comprising the following steps:
[0008] S10, providing a CuAgYSi alloy material, and processing the CuAgYSi alloy material into a heat sink shell structure;
[0009] S20, sequentially performing Mn plating and heat treatment on the vapor chamber shell structure to obtain a vapor chamber shell structure plated with a Mn layer, wherein the vapor chamber shell structure is made of a CuAgYSiMn alloy material;
[0010] S30, using acid solution to dealloy the CuAgYSiMn alloy material to remove the Mn element, and performing post-treatment to obtain a porous CuAgYSi composite material, that is, a high thermal conductivity heat sink composite material.
[0011] As a preferred solution of the method for preparing the high thermal conductivity vapor chamber composite material, step S20 specifically includes:
[0012] S20a, using a PVD process under vacuum to plate Mn onto the alloy surface of the heat sink shell, including the inner surface and the outer surface;
[0013] S20b, heat-treating the vapor chamber shell after the treatment in step S20a under a nitrogen protective atmosphere, so that the Mn element penetrates into the CuAgYSi alloy to form a CuAgYSiMn alloy;
[0014] The heat treatment process conditions are 600°C for 1-2h.
[0015] As a preferred solution of the method for preparing the high thermal conductivity vapor chamber composite material, step S30 specifically includes:
[0016] S30a, immersing the CuAgYSiMn alloy in an acid solution to remove the Mn element;
[0017] S30b, washing the CuAgYSi alloy from which the Mn element has been removed, and vacuum drying to obtain a high thermal conductivity vapor chamber composite material;
[0018] The acid solution is hydrochloric acid with a mass fraction of 6%.
[0019] As a preferred solution for the preparation method of the high thermal conductivity vapor chamber composite material, in step S10, the CuAgYSi alloy material is composed of the following raw materials by mass fraction: Ag, 1.0-5.0wt%; Y, 0.2-0.4wt%; Si, 0.2-0.4wt%; and the balance is Cu.
[0020] As a preferred solution for the preparation method of the high thermal conductivity vapor chamber composite material, the preparation method of the CuAgYSi alloy material includes:
[0021] S10a, mixing Ag, Y, Si, and Cu according to mass fractions and performing smelting treatment to obtain a molten copper alloy;
[0022] S10b, casting the molten copper alloy to obtain a copper alloy ingot;
[0023] S10c, performing homogenization annealing treatment on the copper alloy ingot;
[0024] S10d, performing cold working deformation treatment on the copper alloy ingot after homogenization annealing treatment, and then alternately performing multiple aging treatments and multiple cold working deformation treatments to obtain a Cu-Ag-Y-Si alloy material.
[0025] As a preferred solution for the preparation method of the high thermal conductivity heat spreader composite material, step S10a is specifically as follows: first, Cu and Ag are mixed and heated to melt, and then Si and Y are added in sequence. After sufficient stirring under the protection of inert gas, the slag is skimmed to obtain a pure melt, the furnace temperature is controlled to be 1450-1500°C, and the molten copper alloy is obtained after melting.
[0026] As a preferred solution of the method for preparing the high thermal conductivity vapor chamber composite material, in step S10b, the casting temperature is 1250-1350°C;
[0027] Step S10c specifically includes: subjecting the copper alloy ingot to homogenization annealing treatment in a nitrogen atmosphere at a temperature of 950-980° C. for 4-8 hours.
[0028] As a preferred solution of the method for preparing the high thermal conductivity vapor chamber composite material, step S10d specifically includes the following steps:
[0029] S10a1, subjecting the homogenized copper alloy ingot to cold working deformation treatment, so that the deformation amount is greater than 75%;
[0030] S10a2, performing aging treatment and cold working deformation treatment on the copper alloy treated in step S10a1 in sequence, so that the deformation amount is greater than 75%;
[0031] S10a3, performing aging treatment and cold working deformation treatment on the copper alloy after the treatment in step S10a2 in sequence, so that the deformation amount is greater than 60%;
[0032] S10a4, performing three-level aging and cold working deformation treatments on the copper alloy treated in step S10a3 in sequence, with the deformation amount being 50%, to obtain a CuAgYSi alloy material.
[0033] As a preferred solution of the method for preparing the high thermal conductivity vapor chamber composite material, the aging treatment in step S10a2 is carried out under a nitrogen protective atmosphere at a temperature of 500-650° C. for a time of 1-2 h;
[0034] The aging treatment in step S10a3 is carried out under a nitrogen protective atmosphere at a temperature of 450-650° C. for a time of 1-2 h;
[0035] The aging treatment in step S10a4 is carried out under a nitrogen protective atmosphere at a temperature of 420-480° C. for a time of 1-2 h.
[0036] On the other hand, a high thermal conductivity vapor chamber composite material is provided, which is prepared by the preparation method of the high thermal conductivity vapor chamber composite material.
[0037] Beneficial effects of the present invention:
[0038] 1) The preparation method of the present invention can be used to prepare a porous high thermal conductivity vapor chamber composite material with small-scale interconnected pores inside. The material has an extremely high specific surface area and can be fully in contact with the working liquid. The preparation method of the present invention can greatly improve the thermal conductivity efficiency of the vapor chamber.
[0039] 2) The CuAgYSi alloy material of the present invention contains Ag, Y, and Si elements in a specific ratio, which can form an AgYSi fiber phase. The combined addition of rare earth Y and Si is more conducive to the precipitation of the Ag phase in the CuAgYSi alloy material on the basis of further degassing and deoxidation of the purified alloy melt.
[0040] 3) The preparation method of the present invention is simple, has low equipment requirements, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a cast microstructure morphology diagram of the copper alloy ingot described in Example 1 of the present invention.
[0042] Figure 2 This is a microstructural morphology diagram of the dealloyed porous layer in Example 1 of the present invention. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0044] Unless otherwise specified, various raw materials of the present invention can be purchased commercially or prepared according to conventional methods in the art.
[0045] Example 1 Preparation of high thermal conductivity vapor chamber composite material:
[0046] Step 1: Preparation of CuAgYSi alloy material
[0047] Electrolytic copper is mixed with pure silver, pure silicon, and pure yttrium in the following proportions: Ag: 2.0wt%, Si: 0.3wt%, Y: 0.3wt%, and the balance is Cu. Electrolytic copper and silver are heated and melted in a graphite crucible using an induction furnace, silicon is added, and finally the rare earth element yttrium is added. Under a nitrogen protective atmosphere, the mixture is fully stirred and then slag is removed again to obtain a pure melt. The furnace temperature is controlled at 1450-1500°C. The molten copper alloy is cooled to 1250°C and then cast to obtain a copper alloy ingot. The cast structure photo of the copper alloy ingot is shown in FIG. Figure 1 shown.
[0048] The copper alloy ingot is homogenized annealed at 950℃ for 8h in a protective atmosphere; the homogenized ingot is cold-worked with 80% deformation; the alloy is aged at 600℃ for 1h in a nitrogen protective atmosphere; and then cold-worked with 80% deformation. Then, the aging treatment is carried out in a nitrogen protective atmosphere at a temperature of 500℃ for 2h; the aged alloy is cold-worked again with 50% deformation, and then a three-level aging treatment is carried out in a nitrogen protective atmosphere at a temperature of 450℃ for 2h; the aged plate is cold-worked again with 50% deformation to obtain a CuAgYSi alloy material.
[0049] The tensile strength and elongation of the CuAgYSi alloy material of this embodiment were tested according to "GB / T228.1-2010 Metal Material Tensile Test Part 1: Room Temperature Test Method"; the thermal conductivity of the CuAgYSi alloy material of this embodiment was tested according to "GB / T3651-2008 Metal High Temperature Thermal Conductivity Measurement Method". The tensile strength of the CuAgYSi alloy material was measured to be 627MPa, the elongation was 6.8%, and the thermal conductivity was 395W / (m·K).
[0050] Step 2: Mn plating and Mn removal
[0051] The CuAgYSi alloy material is processed into a vapor chamber shell structure, a nano-scale Mn layer is plated onto the vapor chamber shell structure under vacuum using a PVD process, and heat treated at 600° C. for 1 h under gas protection.
[0052] The heat spreader shell structure was dealloyed with a 6% hydrochloric acid solution and soaked for 10 hours to remove the Mn element. It was fully rinsed with deionized water and vacuum dried to obtain a porous high thermal conductivity heat spreader composite material with small-scale interconnected pores inside.
[0053] The thermal conductivity of the obtained high thermal conductivity vapor chamber composite material is 2.2 times higher than that of the pure copper substrate combined with copper powder design. Combined with water as the cooling medium, its equivalent thermal conductivity is 1520W / (m·K).
[0054] The microstructure of the porous high thermal conductivity heat sink composite material of this embodiment is as follows: Figure 2 shown.
[0055] Example 2 Preparation of high thermal conductivity vapor chamber composite material:
[0056] Step 1: Preparation of CuAgYSi alloy material
[0057] Electrolytic copper is mixed with pure silver, pure silicon and pure yttrium in the proportion of Ag: 5.0wt%, Si: 0.4wt%, Y: 0.4wt% and the balance is Cu. Electrolytic copper and silver are heated and melted in a graphite crucible using an induction furnace, silicon is added, and finally rare earth element yttrium is added. Under a nitrogen protective atmosphere, the mixture is fully stirred and then slag is removed again to obtain a pure melt, and the furnace temperature is controlled at 1450-1500°C. The molten copper alloy is cast when the temperature is cooled to 1250°C.
[0058] The copper alloy ingot was homogenized and annealed at 950℃ for 8h in a nitrogen protective atmosphere; the homogenized ingot was cold deformed with 80% deformation; the alloy was aged at 600℃ for 1h in a nitrogen protective atmosphere; and then cold deformed with 80% deformation. Then, the aging treatment was carried out in a nitrogen protective atmosphere at a temperature of 500℃ for 2h; the aged alloy was cold deformed again with 50% deformation, and then a three-level aging treatment was carried out in a nitrogen protective atmosphere at a temperature of 450℃ for 2h; the aged plate was cold deformed again with 50% deformation to obtain a CuAgYSi alloy material.
[0059] The tensile strength and elongation of the CuAgYSi alloy material of this embodiment were tested according to "GB / T228.1-2010 Metal Material Tensile Test Part 1: Room Temperature Test Method"; the thermal conductivity of the CuAgYSi alloy material of this embodiment was tested according to "GB / T3651-2008 Metal High Temperature Thermal Conductivity Measurement Method". The tensile strength of the CuAgYSi alloy material was measured to be 703MPa, the elongation was 8.3%, and the thermal conductivity was 381W / (m·K).
[0060] Step 2: Mn plating and Mn removal
[0061] The CuAgYSi alloy material is processed into a vapor chamber shell structure, nano-scale Mn is plated onto the vapor chamber shell structure under vacuum using a PVD process, and heat treated at 600° C. for 1.5 h under gas protection.
[0062] The heat spreader shell structure was dealloyed with a 6% hydrochloric acid solution and soaked for 15 hours to remove the Mn element. It was fully rinsed with deionized water and vacuum dried to obtain a porous high thermal conductivity heat spreader composite material with small-scale interconnected pores inside.
[0063] The thermal conductivity of the obtained high thermal conductivity vapor chamber composite material is 2.5 times higher than that of the pure copper substrate combined with copper powder. When combined with water as the cooling medium, its equivalent thermal conductivity is 1850 W / (m·K).
[0064] Comparative Example 1
[0065] The following process is used to prepare pure copper substrate combined with copper powder:
[0066] The copper powder and pure copper are diffused and sintered at high temperature to obtain the pure copper substrate assembled copper powder. The sintering temperature is 950℃, and a certain amount of hydrogen protection is used to combine the copper powder and the pure copper substrate together, and the pores between the copper powders are used to increase the contact area with the cooling medium.
[0067] The strength of the pure copper substrate combined with the copper powder is not enough, and the pure copper is prone to expansion and deformation during the water phase change process.
[0068] According to tests, the tensile strength of pure copper substrate and copper powder is generally no more than 400MPa, which is much lower than that of CuAgYSi alloy material (700MPa). The thermal conductivity of pure copper is 380W / (m·K), which is not much different. Limited by the strength value, combined with water as the cooling medium, its equivalent thermal conductivity is 950W / (m·K).
[0069] The above embodiments are only used to illustrate the detailed methods of the present invention. The present invention is not limited to the above detailed methods, that is, it does not mean that the present invention must rely on the above detailed methods to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a high thermal conductivity vapor chamber composite material, characterized in that: The following steps are involved: S10, providing a CuAgYSi alloy material, and processing the CuAgYSi alloy material into a heat sink shell structure; S20, sequentially performing Mn plating and heat treatment on the vapor chamber shell structure to obtain a vapor chamber shell structure plated with a Mn layer, wherein the vapor chamber shell structure is made of a CuAgYSiMn alloy material; S30, using acid solution to dealloy the CuAgYSiMn alloy material to remove the Mn element, and performing post-treatment to obtain a porous CuAgYSi composite material, that is, a high thermal conductivity heat sink composite material.
2. The method for preparing a high thermal conductivity vapor chamber composite material according to claim 1, characterized in that: Step S20 specifically includes: S20a, using a PVD process to plate Mn onto the alloy surface of the heat sink shell under vacuum; S20b, heat-treating the vapor chamber shell after the treatment in step S20a under a nitrogen protective atmosphere, so that the Mn element penetrates into the CuAgYSi alloy to form a CuAgYSiMn alloy; The heat treatment process conditions are 600°C for 1-2h.
3. The method for preparing a high thermal conductivity vapor chamber composite material according to claim 1, characterized in that: Step S30 specifically includes: S30a, immersing the CuAgYSiMn alloy in an acid solution to remove the Mn element; S30b, washing the CuAgYSi alloy from which the Mn element has been removed, and vacuum drying to obtain a high thermal conductivity vapor chamber composite material; The acid solution is hydrochloric acid with a mass fraction of 6%.
4. The method for preparing a high thermal conductivity vapor chamber composite material according to claim 1, characterized in that: In step S10, the CuAgYSi alloy material is composed of the following raw materials by mass fraction: Ag, 1.0-5.0wt%; Y, 0.2-0.4wt%; Si, 0.2-0.4wt%; and the balance is Cu.
5. The method for preparing a high thermal conductivity vapor chamber composite material according to claim 4, characterized in that: The preparation method of CuAgYSi alloy material comprises: S10a, mixing Ag, Y, Si, and Cu according to mass fractions and performing smelting treatment to obtain a molten copper alloy; S10b, casting the molten copper alloy to obtain a copper alloy ingot; S10c, performing homogenization annealing treatment on the copper alloy ingot; S10d, performing cold working deformation treatment on the copper alloy ingot after homogenization annealing treatment, and then alternately performing multiple aging treatments and multiple cold working deformation treatments to obtain a Cu-Ag-Y-Si alloy material.
6. The method for preparing a high thermal conductivity vapor chamber composite material according to claim 5, characterized in that: Step S10a is specifically as follows: first, Cu and Ag are mixed, heated and melted, and then Si and Y are added in sequence. After sufficient stirring under the protection of inert gas, the slag is skimmed to obtain a pure melt, and the furnace temperature is controlled to be 1450-1500° C., and a molten copper alloy is obtained after melting.
7. The method for preparing a high thermal conductivity vapor chamber composite material according to claim 5, characterized in that: In step S10b, the casting temperature is 1250-1350°C; Step S10c specifically includes: subjecting the copper alloy ingot to homogenization annealing treatment in a nitrogen atmosphere at a temperature of 950-980° C. for 4-8 hours.
8. The method for preparing a high thermal conductivity vapor chamber composite material according to claim 5, characterized in that: Step S10d specifically includes the following steps: S10a1, subjecting the homogenized copper alloy ingot to cold working deformation treatment, so that the deformation amount is greater than 75%; S10a2, performing aging treatment and cold working deformation treatment on the copper alloy treated in step S10a1 in sequence, so that the deformation amount is greater than 75%; S10a3, performing aging treatment and cold working deformation treatment on the copper alloy after the treatment in step S10a2 in sequence, so that the deformation amount is greater than 60%; S10a4, performing three-level aging and cold working deformation treatments on the copper alloy treated in step S10a3 in sequence, with the deformation amount being 50%, to obtain a CuAgYSi alloy material.
9. The method for preparing a high thermal conductivity vapor chamber composite material according to claim 5, characterized in that: The aging treatment in step S10a2 is carried out under a nitrogen protective atmosphere at a temperature of 500-650° C. for a time of 1-2 h; The aging treatment in step S10a3 is carried out under a nitrogen protective atmosphere at a temperature of 450-650° C. for a time of 1-2 h; The aging treatment in step S10a4 is carried out under a nitrogen protective atmosphere at a temperature of 420-480° C. for a time of 1-2 h.
10. A high thermal conductivity vapor chamber composite material, characterized in that: The composite material is prepared by the method for preparing a high thermal conductivity vapor chamber composite material according to any one of claims 1 to 9.